Weryfikacja modelu jednowskaźnikowego dla spółek z indeksu WIG20 - Karpio, Andrzej; Żebrowska-Suchodolska, Dorota (The Verification of the Single-Index Model for Stocks from WIG20, 2005)
The authors try to apply the single-index model for seventeen stocks from WIG20 - one with the indexes of Polish Stocks Exchange. The investigations have concerned the period of time from 29th December 2000 year to 24th December 2004 year. Parameters have been estimated using ordinary least squares method (OLS). The statistical verification of the model shows that OLS is not adequate method of the estimation of the single-index model parameters. It seems that the next step in building of the model should be the estimation of structural parameters performed for shorter periods of time then four years. It may take into consideration the periods of rising and falling stock market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 252-259